2018
DOI: 10.1111/pcn.12670
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphologic changes in early stages of psychosis: Implications for clinical application and early intervention

Abstract: To date, a large number of magnetic resonance imaging (MRI) studies have been conducted in schizophrenia, which generally demonstrate gray matter reduction, predominantly in the frontal and temporo-limbic regions, as well as gross brain abnormalities (e.g., a deviated sulcogyral pattern). Although the causes as well as timing and course of these findings remain elusive, these morphologic changes (especially gross brain abnormalities and medial temporal lobe atrophy) are likely present at illness onset, possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 199 publications
(335 reference statements)
4
56
0
Order By: Relevance
“…Our pituitary findings are generally in line with previous MRI studies in clinical high-risk subjects; the individuals who later develop psychosis may exhibit pituitary expansion prior to psychosis onset ( 10 , 40 ), but those without psychosis onset also have similar pituitary changes ( 10 , 11 ). Although some high-risk studies did not replicate these findings ( 7 , 47 ), probably due to small sample sizes and/or differences in various influencing factors as described below, pituitary expansion reported in psychosis is thought to reflect HPA hyperactivity and a subsequent increase in the size and number of corticotrophs, whereas chronic HPA activation could cause pituitary atrophy by reducing the function of the cells producing other pituitary hormones ( 15 , 48 ). Thus, the pituitary volume in the course of psychosis likely reflects state-related HPA axis dysregulation, which is associated with illness stages and symptom severity ( 15 ), antipsychotic medication ( 2 , 49 ), demographic characteristics [e.g., age, gender ( 50 , 51 )], and other mediating factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our pituitary findings are generally in line with previous MRI studies in clinical high-risk subjects; the individuals who later develop psychosis may exhibit pituitary expansion prior to psychosis onset ( 10 , 40 ), but those without psychosis onset also have similar pituitary changes ( 10 , 11 ). Although some high-risk studies did not replicate these findings ( 7 , 47 ), probably due to small sample sizes and/or differences in various influencing factors as described below, pituitary expansion reported in psychosis is thought to reflect HPA hyperactivity and a subsequent increase in the size and number of corticotrophs, whereas chronic HPA activation could cause pituitary atrophy by reducing the function of the cells producing other pituitary hormones ( 15 , 48 ). Thus, the pituitary volume in the course of psychosis likely reflects state-related HPA axis dysregulation, which is associated with illness stages and symptom severity ( 15 ), antipsychotic medication ( 2 , 49 ), demographic characteristics [e.g., age, gender ( 50 , 51 )], and other mediating factors.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine studies in schizophrenia ( 1 , 2 ) and clinical high-risk subjects for developing psychosis [i.e., at-risk mental state; ARMS ( 3 , 4 )] ( 5 7 ) have reported hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis, which mediates the stress response by governing the release of steroids (e.g., cortisol) and also regulates a number of physiological and neurobehavioral processes (e.g., immunity, fertility, anxiety, and cognitive functioning) ( 8 , 9 ), implying the role of hormonal dysregulation during the course of psychosis. Previous magnetic resonance imaging (MRI) studies in schizophrenia and related psychoses have generally reported enlarged volume of the pituitary gland, an integral part of the HPA axis, prior to psychosis onset ( 10 , 11 ), along with ongoing expansion early in the course of schizophrenia ( 12 , 13 ), which was associated with the emergence of psychosis and the early course of clinical symptoms ( 14 , 15 ). However, some discrepant findings, such as an even smaller pituitary volume in antipsychotic-naïve schizophrenia patients with recent onset ( 16 ) or normal pituitary volume both in patients with first-episode schizophrenia and individuals with ARMS ( 7 ), have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…5 It seems increasingly likely that there are differences in volume even before the at-risk mental state, although this remains difficult to prove definitively. [6][7][8] Recently developed scientific techniques such as the use of induced pluripotent stem cells to create a 'cortex in a dish' (aka brain organoids) have allowed tantalising insights into why these imaging abnormalities may emerge. Using cells from individuals with schizophrenia (some with a range of predisposing genetic abnormalities) multiple studies have shown abnormalities such as impaired cellular differentiation and synapse formation.…”
Section: Brain Imaging and Schizophreniamentioning
confidence: 99%
“…2 The prevalence of informal caring in the underage population was estimated as a minimum of 2-4% in Western countries. 6 Dearden and Becker reported that most young carers cared for parents, particularly mothers, although some provided support for grandparents, siblings or other relatives.…”
Section: Introductionmentioning
confidence: 99%
“…With the advances in technology, vast amounts of neuroimaging data has been generated; however, data mining or signal processing methods so far have limited success in terms of finding reliable diagnostic imaging biomarkers for many psychiatric disorders [4,8]. One of the reasons for this limited success has been the fact that data fusion is a particularly challenging task when the goal is to extract reproducible and interpretable patterns.…”
Section: Introductionmentioning
confidence: 99%